Xanthone from the Fruits of Terminalia Arjuna - Hossain, R.; Sultana, R.; Choudhary, M. I.; Zaman, S. (Journal of Scientific Research, 2016)
2,7-dimethoxyxanthone (1) along with a well known compound ?-sitosterol-3-O-?-D-glucopyranoside (2) were isolated from the methonalic extract of the fruits of Terminalia arjuna. Their structures were elucidated by spectroscopic (NMR and mass) analysis.